Analysis of Formalin Content in Fish Meatballs Traded in Lembang Market, West Bandung Regency - Ani Haerani; Suci Rizki Nurul Aeni; Muhammad Iqbal Alfirmansyah (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2022)
ABSTRACT Background: Meatballs are a type of food that is generally round in shape made from protein- containing mixed with tapioca flour found in Indonesian cuisine. Fish meatballs are easily decomposed, therefore they are preserved with a chemical substance, namely Formalin. Research objective: This study aims to determine the level of formalin in fish balls that are traded in Lembang Market, West Bandung Regency. Research Methods: The study used a descriptive design. The sample in this study amounted to 20 samples of fish balls and the sampling technique was simple random sampling. The test used is a qualitative test and a quantitative test. Results: A total of 1 positive sample used formalin, with an average level of 1.4592 ppm and as many as 19 negative samples did not use formalin. Conclusion: There are still fish balls at Lembang Market, West Bandung Regency which contain formaldehyde